Correlation of multiple lipid and lipoprotein ratios with nonalcoholic fatty liver disease in patients with newly diagnosed type 2 diabetic mellitus: A retrospective study - Li, Ran; Kong, Dehong; Ye, Zhengqin; Zong, Guannan; Hu, Kerong; Xu, Wei; Fang, Ping; Zhang, Liya; Zhou, Yun; Zhang, Keqin; Xue, Ying (Frontiers in Endocrinology, 2023)
Background and Objective: The diagnostic value of lipid and lipoprotein ratios for NAFLD in newly diagnosed T2DM remains unclear. This study aimed to investigate the relationships between lipid and lipoprotein ratios and the risk of NAFLD in subjects with newly diagnosed T2DM. Methods: A total of 371 newly diagnosed T2DM patients with NAFLD and 360 newly diagnosed T2DM without NAFLD were enrolled in the study. Demographics variables, clinical history and serum biochemical indicators of the subjects were collected. Six lipid and lipoprotein ratios, including triglycerides to high-density lipoprotein-cholesterol (TG/HDL-C) ratio, cholesterol to HDL-C (TC/HDL-C) ratio, free fatty acid to HDL-C (FFA/HDL-C) ratio, uric acid to HDL-C (UA/HDL-C) ratio, low-density lipoprotein-cholesterol to HDL-C (LDL-C/HDL-C) ratio, apolipoprotein B to apolipoprotein A1 (APOB/A1) ratio, were calculated. We compared the differences in lipid and lipoprotein ratios between NAFLD group and non-NAFLD group, and further analyzed the correlation and diagnostic value of these ratios with the risk of NAFLD in the newly diagnosed T2DM patients. Results: The proportion of NAFLD in patients with newly diagnosed T2DM increased progressively over the range Q1 to Q4 of six lipid ratios, including the TG/HDL-C ratio, TC/HDL-C ratio, FFA/HDL-C ratio, UA/HDL-C ratio, LDL-C/HDL-C ratio, and APOB/A1 ratio. After adjusting for multiple confounders, TG/HDL-C, TC/HDL-C, UA/HDL-C, LDL-C/HDL-C and APOB/A1 were all strongly correlated with the risk of NAFLD in patients with newly diagnosed T2DM. In patients with newly-onset T2DM, the TG/HDL-C ratio was the most powerful indicator for the diagnosis of NAFLD among all six indicators, with an area under the curve (AUC) of 0.732 (95% CI 0.696–0.769). In addition, TG/HDL-C ratio＞1.405, with a sensitivity of 73.8% and specificity of 60.1%, had a good diagnostic ability for NAFLD in patients with newly diagnosed T2DM. Conclusions: The TG/HDL-C ratio may be an effective marker to help identify the risk of NAFLD in patients with newly diagnosed T2DM.